Analysis of Char Prepared by Pyrolysis of Dabai (Canarium odontophyllum) Nutshells as a Potential Precursor of Biocarbon Used for Wastewater Treatment - Ahmad Adzhar, Mohd Khairulzaim; Rezaur, Rahman; Lidyana, Binti Roslan; Muhammad Khusairy, Bakri; Afrasyab, Khan; Mohammed Mahbubul, Matin (2021)
Dabai (Canarium odontophyllum) nutshells have considerable potential to be used as a viable precursor for biomass-based activated carbon. The material was carbonized at a temperature of 700 °C for 2 h, at a heating rate of 10 °C/min under nitrogen gas flow. The char was analyzed the following ways: percentage of yield, percentage of ash content, Fourier transform infrared spectroscopy, scanning electron microscopy with energy dispersive x-ray analysis, and Brunauer, Emmett, and Teller surface area. The char had a maximum Brunauer, Emmett, and Teller surface area of 428 m2 /g and the nitrogen adsorption-desorption isotherm of the char that was similar to a Type I adsorption isotherm, based on IUPAC classifications. The char also had a high carbon content (up to 93.6%) and a low ash content (3.67%). Therefore, dabai nutshells were found to be a suitable lignocellulosic precursor for the synthesis of activated carbon.